Global Speleothem Oxygen Isotope Measurements Since the Last Glacial Maximum. (26th March 2013) - Shah, A. M.; Morrill, C.; Gille, E. P.; Gross, W. S.; Anderson, D. M.; Bauer, B. A.; Buckner, R.; Hartman, M.
Abstract : This synthesis of thirty-six sites (sixty cores with over 27 000 measurements) located around the world facilitates scientific research on the climate of the last 21 000 years ago obtained from oxygen isotope (δ 18 O or delta-O-18) measurements. Oxygen isotopes in speleothem calcite record the influence of ambient temperature and the isotopic composition of the source water, the latter providing evidence of hydrologic variability and change. Compared to paleoclimate proxies from sedimentary archives, the age uncertainty is unusually small, around +/−100 years for the last 21 000-year interval. Using data contributed to the World Data Center (WDC) for Paleoclimatology, we have created consistently formatted data files for individual sites as well as composite dataset of annual to millennial resolution. These individual files also contain the chronology information about the sites. The data are useful in understanding hydrologic variability at local and regional scales, such as the Asian summer monsoon and the Intertropical Convergence Zone (as discussed in the underlying source publications), and should also be useful in understanding large-scale aspects of hydrologic change since the Last Glacial Maximum (LGM).